Pengembangan Buku Cerita Anak Berbasis Kearifan Ulama Nusantara Sebagai Pendamping Mata Pelajaran Akidah Akhlak Madrasah Ibtidaiyah - Afrida, Fira Nadliratul (Dawuh Guru: Jurnal Pendidikan MI/SD, 2025)
This study aims to develop a Children's Storybook Based on the Wisdom of Nusantara Ulama as a supplementary resource for the Aqidah Akhlak subject in Madrasah Ibtidaiyah In an effort to enhance students' character. considering the low literacy rate in Indonesia. The research method used is Research and Development (RnD) with the ADDIE model, which includes analysis, design, development, implementation, and evaluation. The findings indicate that the developed storybook not only enhances students' reading interest but is also effective in instilling character and moral values taught by Islamic scholars. The validation results from teaching material experts averaged 88.7, subject matter experts 93.7, and instructional experts 82.5, demonstrating that the book is highly suitable for learning. In conclusion, the development of this local wisdom-based storybook significantly contributes to improving reading literacy and character formation among Madrasah Ibtidaiyah students while introducing Islamic history in a contextual manner.